Policy on urban leasing in contemporary Peru - Friz Burga, Johnny Zas (2020)
The article analyzes the urban leasing policy in contemporary Peru and seeks to explain the origin and permanence of contractual interventionism in urban leasing until the 21st century. All political periods are analyzed, from the governments of Augusto Leguía (1919-1930) to the governments of the last democratic transition (2000-2020) and it seeks to show very synthetically the multiple determinations of contractual interventionism. The analysis of public policy on urban leasing is developed within the framework of the contemporary Peruvian urbanization process, defined by the development of the so-called neighborhood as the way through which the urban popular sectors accessed housing from the decade from the fifties of the 20th century and how they were incorporated and integrated into the city; and the parallel weakening of the identification between slum, rental and housing of the urban popular sectors.